ISOLATION OF Salmonella typhoid 16s rRNA GENE FRAGMENT BASED ON POLYMERASE CHAIN REACTION (PCR) - Salman Farisi; Wawan Abdullah Setiawan; Suratman Umar (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2020)
Iridescent is one of the traditional fish fermentation products that has a sour taste and is widely known in various regions of Indonesia. In its metabolism LAB produces organic acids, hydrogen peroxide, diacetyl, CO2 and bacteriocin. These compounds are antimicrobial compounds that inhibit the growth of pathogenic bacteria and bacterial decomposition. The purpose of this study was to determine the antibacterial activity produced by lactic acid bacteria isolates from catfish (Pangasius hypophthalmus) inhibiting the growth of Escherecia coli. From iridescent obtained 9 isolates that have different characteristics from each other by the morphology of LAB isolate colonies which include colony color, colony shape, colony elevation and colony margin. After production of antibacterial, all isolates showed positive result when antibacterial tested againts Escherecia coli either in acidic condition or neutralized.